Pathomechanisms of AERD—Recent Advances - Lyly, Annina; Laidlaw, Tanya M.; Lundberg, Marie (Frontiers in Allergy, 2021)
The pathomechanisms behind NSAID-exacerbated respiratory disease are complex and still largely unknown. They are presumed to involve genetic predisposition and environmental triggers that lead to dysregulation of fatty acid and lipid metabolism, altered cellular interactions involving transmetabolism, and continuous and chronic inflammation in the respiratory track. Here, we go through the recent advances on the topic and sum up the current understanding of the background of this illness that broadly effects the patients’ lives.